Preschool children's consistency of word production. - Holm, Alison; van Reyk, Olivia; Crosbie, Sharon; De Bono, Simone; Morgan, Angela; Dodd, Barbara (Clinical Linguistics & Phonetics, 2023)
Consistency of word production contributes to carers' ability to understand children's speech. Reports of the proportion of words produced consistently by typically developing preschool children, however, vary widely from 17% to 87%. This paper examines the quantitative (consistency count) and qualitative (e.g. phonemic analysis) characteristics of word consistency in 96 children aged 36–60 months. Children named 15 pictures twice, in separate trials, in the same assessment session. The mean consistency of the production for the whole group was 82%. Older children were more consistent than younger children. Girls were more consistent than boys. Words produced correctly in one trial and in error in another may indicate resolving error patterns. Words produced in error in two different ways provided useful evidence about the nature of inconsistent word production in typically developing children. The clinical and theoretical implications are discussed.